Psychometric properties of Turkish version of the problematic gambling severity index in patients with a diagnosis of gambling disorder - Altıntaş, Merih; Tunç, Emine Burcu; Dinçer, Duygu; Özdenler, Merve; Hunca Olcay, Ayşe Nazlı; Barın, Can (Journal of Dependence, 2022)
Objective: The aim of this study was to examine the psychometric properties of the Problematic Gambling Severity Index (PGSI) in a study group consisting of participants with and without a diagnosis of pathological gambling disorder.Method: Data were collected from 539 individuals, 60 of whom were diagnosed with gambling disorder. The Problematic Gambling Severity Index (PGSI), South Oaks Gambling Screening Test (SOGS) and demographic information form were used to collect data. Linguistic equivalence, validity, reliability and item statistics of the index were examined.Results: Construct validity and criterion-related validity analysis were performed for validity estimations. As a result of the confirmatory factor analysis performed to examine the construct validity, it was seen that the structure of the scale consisting of nine items and a single sub-dimension was valid in Turkish culture. To determine criterion-related validity, the relationship between the PGSI and the SOGS was examined. The analysis showed that there was a significant relationship between the two scales. For the reliability estimations, the internal consistency analysis of the index and test-retest reliability were examined. The internal consistency level was calculated with the Cronbach’s alpha coefficient and it was seen that the internal consistency was high. In the test-retest analysis, it was seen that the relationship between the administrations of the scale in the same group at two different times was high.Conclusion: The PGSI is a valid and reliable measurement that can be used both in clinical research and practical studies to be conducted in Turkey, and in survey studies to be conducted on the general population.Keywords: The Problematic Gambling Severity Index (PGSI), problem gambling, validity, reliability, cultural adaptation
Keywords: The Problematic Gambling Severity Index (PGSI); problem gambling; validity; reliability; cultural adaptation